Tinjauan Pustaka: Solusi Keamanan Berbasis Honeypot untuk Menjaga Keamanan Data Kritis di BMKG - Ruth Archana Sihombing; Ni Made Julia Puspa Dewi (Journal of Computation Physics and Earth Science (JoCPES), 2022)
The expanding dependence on advanced foundations by meteorological organizations like BMKG (Badan Meteorologi, Klimatologi, dan Geofisika) has increased the hazard of cyber attacks, which seem compromise basic climate and climate information frameworks. This paper investigates the execution of honeypot-based security arrangements as a proactive approach to defend BMKG's organize framework. Honeypots, outlined to draw potential aggressors, give important bits of knowledge into rising dangers and offer assistance to relieve dangers some time recently they reach center frameworks. By sending honeypots in BMKG's organize, this consider explores their viability in identifying and analyzing cyber-attacks focusing on meteorological information, which is basic for open security and national improvement arranging. The inquire about presents a comparative investigation of different honeypot arrangements and their capacity to distinguish modern dangers, such as zero-day misuses and Progressed Tireless Dangers (APTs), which posture critical dangers to BMKG's operations. Comes about illustrate that joining honeypots into BMKG's cybersecurity system upgrades risk discovery, diminishes reaction time, and reinforces in general information security. These discoveries highlight the potential for honeypot frameworks to play a key part in securing basic meteorological data, guaranteeing the unwavering quality and astuteness of climate information fundamental for calamity readiness and hazard administration.